Translation Shift Of English Noun Phrases Into Indonesian In The Movie Of Enola Holmes - Ni Kadek Sindiasti Rahanita Prativi; Ida Bagus Putra Yadnya; Ida Ayu Made Puspani (CV. Ulil Albab Corp, 2022)
This study is entitled “Translation Shift of English Noun Phrases into Indonesian in the Movie of Enola Holmes”. It was formulated to studying regarding shift of English noun phrases into Indonesian. The data were taken from a movie entitled “Enola Holmes”. As the data involving two languages, the data were taken from two sources in which involving the movie English spoken text and the Indonesian subtitles. It was collected through observation by using note-taking technique concerning shift and translation equivalence undergone by the English noun phrases into Indonesian. The data were then analysed using comparison technique through descriptive qualitative method. The theory used in this study was proposed by Catford regarding translation of shifts. In the process of translation, it was discovered that the result concerning shift have appeared several times within the study in the process of translation of English noun phrases into Indonesian. From the result found in the data analysis, it was discovered that there is changes in terms of structural form between the SL and TL.